2019
DOI: 10.1002/cphc.201900653
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Capping Agents on the Oxygen Reduction Reaction Activity and Shape Stability of Pt Nanocubes

Abstract: We investigated the formation of Pt nanocubes (NCs) and their electrocatalytic oxygen reduction reaction (ORR) properties and structural stability using two different capping agents, namely, polyvinylpyrrolidone (PVP) and oleylamine (OAm). The mono‐dispersity of the obtained Pt NCs and their interactions with PVP and OAm were analyzed by transmission electron microscopy (TEM), energy dispersive X‐ray spectroscopy (EDX), X‐ray photoelectron spectroscopy (XPS), Fourier‐transformed infrared spectroscopy (FTIR) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 50 publications
0
57
0
Order By: Relevance
“… 44 A reasonable possibility is oxidation of the capping agent oleylamine, since it has been reported that oleylamine is unstable during electrochemical cycling at potentials higher than 1.0 V per RHE. 45 These results emphasize the benefits of operando imaging methods: electrochemical analysis alone does not readily distinguish between Ni dissolution and side reactions such as oxidation of capping agents, whereas images are most sensitive to the removal of metallic species, with changes in the surfactant not highly visible. The combination of electrochemical analysis and in situ imaging provides a more complete picture of the etching process.…”
Section: Resultsmentioning
confidence: 78%
“… 44 A reasonable possibility is oxidation of the capping agent oleylamine, since it has been reported that oleylamine is unstable during electrochemical cycling at potentials higher than 1.0 V per RHE. 45 These results emphasize the benefits of operando imaging methods: electrochemical analysis alone does not readily distinguish between Ni dissolution and side reactions such as oxidation of capping agents, whereas images are most sensitive to the removal of metallic species, with changes in the surfactant not highly visible. The combination of electrochemical analysis and in situ imaging provides a more complete picture of the etching process.…”
Section: Resultsmentioning
confidence: 78%
“…This implies that only the product distribution (ratio of FECO and FEH2 values) is altered by this treatment, whereas the total current density normalized to the geometric surface area (total transferred charge) remains unaffected. This is an important distinction between the current study and previous studies on catalyst activation processes in which only a single electrocatalytic reaction needs to be considered (e.g., ORR 40,49,55 , OER 49 , or HER 37 ) and where increased reaction rates directly correlate with an increase of the electrochemically active surface area (ECSA). [53][54] In order to elaborate on which experimental factors contribute to the observed change in the product distribution (e.g.…”
Section: Resultsmentioning
confidence: 98%
“…Chemisorbed PVP ligands were reported to enhance the catalytic activity in the liquid phase reaction by stabilizing the metal nanocrystals [ 57 ]. The pyrrolidone ring of chemisorbed PVP interacts with the Pt surface and that interaction can serve as the electron donor–acceptor media between PVP and the Pt surface [ 58 ]. However, the interaction of PVP ligands with the metal via the O atom in the ring can accompany the charge transfer from PVP to the metal, and the PVP interaction via the N atom in the ring can accompany the charge transfer from the metal to PVP [ 59 ].…”
Section: Resultsmentioning
confidence: 99%